Pengembangan Teori dan Model Pembelajaran Scrapbook di MI NU An Nur Purworejo - Syta Acetylena; Adib Qosim M; Ahmad Zakaria; Qomaruzzaman Qomaruzzaman (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to develop a creative and contextual scrapbook-based learning model suited to the characteristics of MI students, and to examine its effectiveness in improving motivation and conceptual understanding. The need for innovative learning media arises because existing visual media have not sufficiently integrated cognitive, affective, and character-building aspects. The Research and Development (R&D) method was employed through stages of needs analysis, model design, expert validation, and limited trials. The research subjects consisted of education experts, MI teachers, and 26 fourth-grade students at MI NU An Nur Purworejo. The instruments used included expert validation sheets, observation sheets, questionnaires, and concept-understanding tests. The hypothesis tested whether the scrapbook significantly improved students’ understanding. The results showed an increase in pretest–posttest scores, excellent model implementability, and positive responses from both students and teachers. These findings indicate that scrapbook functions not only as a visual medium but also as a learning model that promotes active engagement and supports the internalization of character values through the SQ–IQ–EQ framework. This study contributes to the development of innovative learning models in MI and emphasizes the importance of integrating creative visual media to enhance the quality of learning.